2014
DOI: 10.5603/ait.2014.0050
|View full text |Cite
|
Sign up to set email alerts
|

Zasady podawania leków przez sztuczny dostęp odżywczy do przewodu pokarmowego — terra incognita intensywnej terapii?

Abstract: The use of enteral feeding tubes has become more frequent, both in hospital settings and in home care. The feeding tubes serve not only to deliver nutrients, but also as a route for medication provision. Nonetheless, the pharmaceutical, legal and technical implications of medication delivery via enteral feeding tubes are not widely understood by doctors and nurses. Not only is the type of medication relevant, but also the type of feeding tube. Crushing tablets may have detrimental effects for a patient and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…Although the situation is not as critical as Matysiak‐Luśnia and Łysenko from Poland stated in 2014, 2 the present study demonstrated that more than half (52%) of the used medications lack information from manufacturers regarding formulation alteration, such as crushing, nor specific instructions for administering via FTs.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Although the situation is not as critical as Matysiak‐Luśnia and Łysenko from Poland stated in 2014, 2 the present study demonstrated that more than half (52%) of the used medications lack information from manufacturers regarding formulation alteration, such as crushing, nor specific instructions for administering via FTs.…”
Section: Discussioncontrasting
confidence: 47%
“…The use of enteral feeding tubes (FTs) for medication administration has become common in the case of patients who cannot swallow food and medications safely. [1][2][3][4] There is general awareness that all drug formulations are not suitable for this, 1,[3][4][5][6] but there is still insufficient evidence on medications that are safe and effective if administered via FTs. 1,3,4,7,8 Furthermore, the availability of more suitable dosage forms, such as liquids, might be a problem, 9 especially on a small pharmaceutical market as there is in Estonia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, drug administration via enteral feeding tubes may be necessary for COVID-19 patients. Once again, crushed tablets may result in clogged tubing, leading to increased adverse events and decreased medication efficacy [20] .…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, crushing ART can be crucial to avoid missed doses. Previous studies have demonstrated that incorrect administration of oral medication through an EFT is a frequent cause of medication errors, resulting in increased toxicity or decreased effectiveness [ 3 ]. Case studies and series describe successful use of crushed dolutegravir (DTG)-based regimens, which guided our hospital's use of this crushed therapy [ 4–9 ].…”
mentioning
confidence: 99%